Association of anthropometric parameters with intelligence quotient in early school-aged children: a cross-sectional study in Iran - Kimia Mahjubi; Mohammad Effatpanah; Mohammadamin Parsaei; Sayed Yousef Mojtahedi; Anahita Izadi; Reza Tavakolizadeh (BMC Pediatrics)
Abstract Background While the link between body growth indices in the first three years of life and neurodevelopment is well established, the relationship between these indicators and intelligence levels in later stages is not well understood. This study aimed to investigate the association between various anthropometric indices and Intelligence Quotient in early school-aged children. Methods This cross-sectional study recruited healthy students aged 7 to 8 years from four primary schools in Tehran, Iran. Measurements included body weight, height, body mass index, arm circumference, waist circumference, and hip circumference. Intelligence Quotient was assessed using the Raven's Standard Progressive Matrices Test, with scores standardized by age according to the Raven's manual. Separate univariate linear regression analyses evaluated the association between each anthropometric index and children’s Intelligence Quotient scores. Multivariate linear regression analyses were then performed to adjust for potential confounding factors, including the child's sex, age, and parental education levels. Results A cohort of 160 children (80 females), with a mean age of 7.5 ± 0.6 years, was included in the study. The participants exhibited the following mean anthropometric values: weight 27.7 ± 6.5 kg, height 1.2 ± 0.1 m, body mass index 17.9 ± 3.4 kg/m2, arm circumference 20.7 ± 2.8 cm, waist circumference 56.4 ± 6.4 cm, and hip circumference 68.1 ± 6.6 cm. Their mean Intelligence Quotient score was 106 ± 16.6. In the univariate analysis, children's weight was not significantly associated with Intelligence Quotient score (P-value = 0.153, β = 0.288 [-0.108, 0.684]), while height was negatively associated (P-value = 0.048, β = -31.685 [-63.142, -0.228]) and body mass index showed a positive association (P-value = 0.001, β = 1.265 [0.524, 2.006]). Abdominal circumference was not significantly associated with Intelligence Quotient (P-value = 0.913, β = 0.051 [-0.870, 0.972]), but both waist circumference (P-value = 0.007, β = 0.542 [0.147, 0.937]) and hip circumference (P-value = 0.013, β = 0.484 [0.102, 0.866]) demonstrated significant positive associations with Intelligence Quotient. However, none of the anthropometric indices maintained statistically significant associations with Intelligence Quotient after adjusting for potential confounders (P-values > 0.05). Conclusions This study indicated no strong relationship between various body measurements and intelligence levels in school-aged children after adjusting the analyses for confounders. This suggests that intelligence in these children may be largely shaped by genetic and sociodemographic factors, with minimal influence from physical growth patterns.